Do Digital Visual Aids Improve Skin Self-Examination Behaviours? A Systematic Review - Heba Abdalla; Johanna Joyce; Nurul Amanina Binte Hussain; Monika Janda (Health Education & Behavior, 2026)
Digital visual aids like smartphone applications can potentially increase uptake and maintenance of Self-Skin Examination (SSE) behaviours, which is an essential secondary prevention strategy for early detection of skin cancer. This review aimed to understand whether digital visual aids with lesion monitoring functions improve SSE behaviours without negatively impacting health outcomes. A systematic search was performed using six databases for relevant literature published before June 2025. Studies were included if they used digital interventions that could monitor skin lesions and reported outcomes on SSE behaviours or their antecedents, such as SSE knowledge, attitudes and intentions. Data were analysed following an adapted Technological Acceptance Model framework. Twenty studies conducted in the United States, the United Kingdom, or Australia involving 19 to 1,000 participants were included. Nineteen studies were randomised controlled trials (RCTs) or nested within RCTs, with one non-nested cross-sectional study. Interventions were delivered by smartphone and/or tablet applications, or websites. Studies found digital visual aids led to improved knowledge ( n = 6), perceived usefulness ( n = 5), ease of use ( n = 7), attitudes towards SSE ( n = 13), as well as intention to perform regular SSE ( n = 5). Overall, there was a positive impact on health outcomes, with only two studies reporting an increase in anxiety and worry following the intervention. Three of seven studies demonstrated an increased likelihood of detecting malignant skin lesions when monitoring using digitally aided SSE. There is potential for digital visual aids to improve SSE behaviours. However, it is important to address barriers to the use of digital visual aids for SSE and to improve their integration with clinical care.